TEORI PERTUMBUHAN BASIS EKSPOR: PENERAPANNYA UNTUK PERTUMBUHAN REGIONAL DI KABUPATEN JEPARA - Shandy Jannifer Matitaputty (Optimum: Jurnal Ekonomi dan Pembangunan, 2015)
Jepara district is a district that was born from trading activities. This studyintends to analyze the characteristics of Jepara regency economy associated withregional growth theory of export base and see a picture of the application of the theoryof the growth of the export base in Jepara regency. This study uses a model export baseanalysis and sector analysis model base. The results showed the condition of Jepararegency trade balance defi cit should be a concern if you want to implement a growthmodel export base. Community characteristics, expertise woodcarving hereditary, theability to survive in times of crisis, as well as branding of furniture and handicraftcarving that can actually be used as the power demand (exports).